IMPLEMENTASI APLIKASI GAMES EDUKASI DENGAN BAHASA ISYARAT SIBI UNTUK ANAK USIA 5 SAMPAI 9 TAHUN DENGAN HAMBATAN TUNARUNGU BERBASIS ANDROID - Erminah, Erminah; Sofiana, Sofa (CV SWA Anugerah, 2025)
Problems that occur in children aged 5 to 9 years with hearing impairments in recognizing and learning the alphabet, where it is very difficult to find learning media, both books and electronic media, that can be used by children aged 5 to 9 years with hearing impairments. Introduction to the alphabet is the basic key. so that children can read. The library study method is a data collection technique by examining, studying and comparing existing theories or research results, whether from books, journals or other media related to the research being carried out. Observation Method is a method carried out by systematically observing and recording a research subject directly in the field, intended to obtain data naturally. Interviews attempt to obtain information by asking informants directly. The use of this application provides good facilities in the form of educational games and can be applied as a practical and interesting SIBI teaching tool as well as implementing educational applications as learning aids. Implementation of an educational games application using sign language for children aged 5 to 9 years with hearing impairments based on Android makes it easy for educators and students. Based on the descriptions explained in the previous chapters, it can be concluded that this Android-based application provides information about the introduction of SIBI numbers and letters for the hearing impaired. It can be proven from the results obtained in the questionnaire that 85.6% strongly agreed, this shows that the application made was delivered on target